The Effect of CAR, NPL, LDR, and BOPO On ROA in Banking Companies Listed in Indonesia Stock Exchange Period 2011 - 2016 - Josua Stanley; Thomas Firdaus Hutahaean; Roma Uli Angriani Sinaga; Vita; Sonia (Journal of Research in Business, Economics, and Education, 2020)
This test aims to determine how the influence of Capital Adequacy Ratio, Non Performing Loans, Loan to Deposit Ratio and Operating Expenses on Operational Income to Return On Assets. This type of research is quantitative research. The population of the banking sector is 23 companies, over a period of 6 years. The sample technique is purposive random sampling method. The results showed that partially the Capital Adequacy Ratio had a positive and insignificant effect on Return on Assets, Non Performing Loans and Operational Expenses on Operational Income had a negative and significant effect on Return on Assets, Loan to Deposit Ratio had a positive and insignificant effect on Return on Assets. The amount of variation in Return On Assets that can be explained by the independent variables used is 54.1% and 45.9% can be explained by other variables such as Cash Position, and others.